SURASTRI KARMA TRIMURTI: MENGGUGAT HAK-HAK KAUM BURUH PEREMPUAN INDONESIA TAHUN 1945-1954 - Giana Fitri Indraswari; Leli Yulifar (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2018)
This research is entitled “Surastri Karma Trimurti: Sued the Right of Woman Laborers of Indonesia 1945-1954”. This research is the interest of author in the role of S.K Trimurti in defending the rights of women laborers in Indonesia in 1945-1954. The purpose of this research are, 1) Describe the the social-economic woman laborers in Indonesia 1930-1944; 2) Describe the background of S.K Trimurti’s life; 3) Describe how was the efforts of S.K Trimurti for the right of Indonesian woman laborers in 1945-1954; 4) Describe the impact of S.K Trimurti’s struggled on the rights of indonesian woman laborers 1948-1954. This research using the History Method, there are: Heuristics, Critics, and Historiography. The research technic which is used in this paper is literature study by using the relevant books. Based on th research, there was few results. First, The condition of woman laborers during the Dutch and Japanese occupations showed injustice, The condition of women workers is still very apprehensive with various actions that are inconsistent with the dignity of women workers as laborers. Second, some activists who fought for the rights of women laborers as one of the workers were S.K Trimurti who had contributed to the fight before and after independence. Third, the efforts of S.K Trimurti were demonstrated for the welfare and prosecution of justice for women laborers in Indonesia, especially regarding wages and reproductive rights. Fourth is the impact of the struggle was contained in the Work Act of 1948 even until now a legal guideline in the field of labor.